Supportive care medications coinciding with chemotherapy among children with hematologic malignancy - Biltaji, Eman (Leuk Lymphoma, 2020)
Pharmacokinetic (PK) conflicts can arise between supportive care medications (SCM) and chemotherapy in children with hematologic malignancy (HM). In this retrospective study, medical records for children (28 days–18 years) diagnosed with HM and receiving an SCM antimicrobial were collected from a hospital network between 1 May 2000 and 31 December 2014. PK drug-gene associations were obtained from a curated pharmacogenomics database. Among 730 patients (median age of 7.5 (IQR 3.7–13.9) years), primarily diagnosed with lymphoid leukemia (52%), lymphoma (28%), or acute myeloid leukemia (16%), chemotherapy was administered in 2846 hospitalizations. SCM accounted for 90.5% (n = 448) of distinct drugs with 93% (n = 679) of children, receiving ≥5 different SCM/hospitalization. Same-day SCM/chemotherapeutic PK gene overlap occurred in 48.3% of hospitalizations and was associated with age (p = 0.026), number of SCM, HM subtype, surgery, and hematopoietic stem cell transplant (p < 0.0001). A high and variable SCM burden among children with HM receiving chemotherapy poses a risk for unanticipated PK conflicts.